Compliance of patients with Class III malocclusion to orthodontic treatment - Abdulhussein , Zaid Alaa; Aksoy , Alev (Journal of Baghdad College of Dentistry, 2022)
Background: Although the new treatment methods developed in recent years are aiming to minimize the need for cooperation of the patients; however, the latter still important factor the treatment. The aim of the study was to evaluate the cooperation level of Class III maloc-clusion patients with orthodontic treatment. Materials and methods: This study followed a cross-sectional style; the targeted population was patients with Class III malocclusion who were treated with three different types of orthopaedic appliances. Four questionnaires were delivered to the patient, patient’s parents, and orthodontists. Statistical analyses of the study were performed with SPSS 20.0 software. Descriptive analyses were presented using fre-quency, percentage, mean, and standard deviation. Results: The study included a total of 183 orthodontic patients in the final analysis. Slightly more than half of the participants were females (52.46%; n=96) and the rest were male (47.54%; n=87). The highest frequency ac-cording to the device type was FM (50.8%) followed by CC (31.1%) while FM+RME wearer was 18.1%. Male expressed significantly higher (p